Analysis of Indications and Different Surgical Approaches for Gynecological Hysterectomies and their Consequences - Sidra Asif, Seemal Tajasar, Amna Bibi, Muhammad Ilyas Riaz, Khushboo Chandio, Omer Farooq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hysterectomy is one of the most common gynecological surgeries regardless of the surgeon’s approach. Purpose: This study was conducted to compare three hysterectomy techniques, viz abdominal, vaginal and laparoscopic hysterectomy, in terms of their effectiveness and low post-op complications. Methods: The study’s cohort included 631 women who underwent benign hysterectomies between 2018 and 2022 in tertiary care hospitals in three areas of Pakistan. The patients in Groups A, B, and C comprised 277, 43 and 311 patients, who were surgically operated by LHs, VHs, and AHs, respectively. Findings: Most of the patients with BH were of age 39-50 years and multiparous with an average weight of 71.4+15 Kg. The major (p<0.05) underlying medical conditions were endometriosis, followed by uterine bleeding, fibroids, pelvic prolapse, adenomyosis and gynecological cancer having an incidence of 44.05, 36.45, 11.88, 5.38, 1.26 and 0.95%, respectively. The AH and VH had the highest incidence of surgical and post-operative problems (p<0.05) compared to the LH, with percentages of 56.59, 55.81, and 20.21%, respectively. Among complications, most often observed were thrombosis, post-operative infections, and bleeding (p<0.05). Practical implications: It was recommended that the gynaecologist should pursue LH, which is less invasive and has a high success rate, for BH. Conclusion: It was thus concluded that the laparoscopic hysterectomy was minimally invasive and was associated with a low incidence of intraoperative and postoperative complications. Keywords: Endometriosis; Non-invasive hysterectomy; Laparoscopic hysterectomy; Intraoperative complications.